Morphological analysis of erythrocytes of an Antarctic teleost under heat stress: Bias of the stabling effect. (January 2022) - Rizzotti, Damiano; Manfrin, Chiara; Gerdol, Marco; Greco, Samuele; Santovito, Gianfranco; Giulianini, Piero G.
Abstract: The stenothermal Antarctic fish that live in the coastal waters of the Terra Nova Bay (Ross Sea) are rarely exposed to temperatures above zero during the year. We tested whether a slight temperature rise of 1.5 °C affects a sensitive biomarker such as erythrocytes morphology in sections of blood pellets of a small demersal notothen. The erythrocytes' shape descriptors showed significant or highly significant differences temporally from the capture of fish to the conclusion of the experiment. Surprisingly, the erythrocyte's morphology did not show significant differences between the two experimental conditions, returning similar results in control fish stabled at −0.9 °C and in the fish treated at +0.6 °C, although the values of the shape descriptors were often lower in the latter. This study demonstrates the critical issues of comparative physiology in the study of extremely sensitive organisms, such as the fish of the High Antarctic Zone. Moreover, the stabling effect inside the aquarium facilities appears to significantly obscure the effects of the experimental heat treatment. Highlights: Moderate heat stress induces significant changes in erythrocytes' morphology. There are no significant differences between thermal treated fish and controls. Antarctic stenotherm fish reveal extreme sensitivity to acclimation conditions alone.